2014
DOI: 10.1007/s11033-014-3251-1
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of genetic variation of yellow catfish Pelteobagrus fulvidraco Richardso in Huaihe river and the Yangtze river revealed using mitochondrial DNA control region sequences

Abstract: Genetic variability and population genetic structure of the yellow catfish Pelteobagrus fulvidraco Richardso in the Huaihe river and the Yangtze river was examined with a 810-bp of the mitochondrial DNA control region. A total of 70 haplotypes were identified from 145 samples, which were characterized with high haplotype diversity (h = 0.9832 ± 0.0041) but low nucleotide diversity (π = 0.0415 ± 0.0201). The analysis of molecular variance and phylogenetic reconstructions detected significant geographic structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…It has been reported that the Yangtze River system is the center of the natural distribution of yellow catfish, as well as the main culture region of yellow catfish together with the Pearl River system (Chu, Zheng, & Dai, 1999; Li et al, 2018). Population genetics studies based on microsatellites and mtDNA sequences in other studies also found high genetic diversity in the Yangtze River, as we report here (Guo, Guo, et al, 2019; Xiao et al, 2014). However, low or moderate genetic diversity has also been reported (Li et al, 2009; Liu et al, 2016; Liu, Zhong, & Pan, 2013; Zhong et al, 2013, 2018; Zhou et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It has been reported that the Yangtze River system is the center of the natural distribution of yellow catfish, as well as the main culture region of yellow catfish together with the Pearl River system (Chu, Zheng, & Dai, 1999; Li et al, 2018). Population genetics studies based on microsatellites and mtDNA sequences in other studies also found high genetic diversity in the Yangtze River, as we report here (Guo, Guo, et al, 2019; Xiao et al, 2014). However, low or moderate genetic diversity has also been reported (Li et al, 2009; Liu et al, 2016; Liu, Zhong, & Pan, 2013; Zhong et al, 2013, 2018; Zhou et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…The population genetic structure pattern among populations in this study is comparable with those reported previously for the yellow catfish. Based on the mtDNA sequences and microsatellite loci analyses, no obvious genetic differentiation was detected among the populations in the Yangtze River and the Pearl River systems, but significant genetic differentiation was detected between populations in Yangtze River and the other populations not in the Yangtze River (Guo, Guo, et al, 2019; Ku, Zhou, & He, 2010; Li et al, 2009; Xiao et al, 2014; Yang, Mayden, & He, 2009; Zhong et al, 2013, 2018; Zhou et al, 2016). The conclusions presented herein may be more accurate and confirm the population genetic structure of yellow catfish in China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of yellow catfish was about 300 thousand tons in 2013, with annual increase between 15 and 20 % in recent years. However, overfishing and pollutions from pesticides and industrial wastewater have seriously reduced the natural populations of yellow catfish (Xiao et al 2014). The breeding parents of yellow catfish are captured from the wild or from the population that has been cultured for several generations.…”
Section: Introductionmentioning
confidence: 99%